2017
DOI: 10.1177/1847980417742304
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-engineered cementitious composites

Abstract: Graphene, a two-dimensional monoatomic thick building block of a carbon allotrope, has emerged as nano-inclusions in cementitious materials due to its distinguished mechanical, electrical, thermal, and transport properties. Graphene nanoplatelet and its oxidized derivative graphene oxide were found to be able to reinforce and modify the cementitious materials from atomic scale to macroscale, and thereby endow them with excellent mechanical properties, durability, and multifunctionality. This article reviews th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 83 publications
3
53
0
1
Order By: Relevance
“…On the other hand, the addition of GO generally decreased the drying shrinkage as the GO content went beyond 0.03%. It was found that GO in the ECC densified microstructure with nano-filler at a microscale helped reduce shrinkage and cracks, with energy absorption during the failure pattern at microscale [ 35 ]. It can be concluded that GO has a more significant influence on the drying shrinkage compared to CR.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the addition of GO generally decreased the drying shrinkage as the GO content went beyond 0.03%. It was found that GO in the ECC densified microstructure with nano-filler at a microscale helped reduce shrinkage and cracks, with energy absorption during the failure pattern at microscale [ 35 ]. It can be concluded that GO has a more significant influence on the drying shrinkage compared to CR.…”
Section: Resultsmentioning
confidence: 99%
“…First, the drying shrinkage of the ECC matrix is lower, leading to eigenstress in the composite when restrained compared to that of normal concretes. Next, regarding compression behavior, due to the absence of coarse aggregates in the ECC the elastic modulus will be lesser than that of conventional concrete as well, resulting in more strain when it attains its compressive strength [ 9 ]. When exposed to elevated temperatures, the performance of the ECC degrades as well.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) (C140.H40.O20) [ 30 ] has been considered one of the most superior graphene derivatives for cementitious composites, because of its significant bonding to various oxygen functional groups and thus exhibiting higher reactivity with cement due to its large surface area [ 31 , 32 ]. The presence of hydrophilic functional groups in GO implies that the composites are still best dispersed [ 9 ]. Graphene is an excellent nanofiller, but is not quite durable and is expensive to modify cement products.…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the fact that the BNP sheets promote the growth of C-S-H, thus less space available for Ca(OH)2 to grow in size. Zheng et al [27] found that when GO is present in the matrix, the size of Ca(OH)2 becomes smaller and the content of C-S-H increases, resulting in a dense structure. It is noteworthy that the addition of 0.40-wt% BNPs and 0.60 wt% BNPs leads to a Ca(OH)2 size higher than that at 0.2 wt BNPs.…”
Section: Influence Of Bnps On the Hydration Phases Of Cementitious Comentioning
confidence: 99%